SIRT1 Suppresses Activator Protein-1 Transcriptional Activity and Cyclooxygenase-2 Expression in Macrophages - Ran Zhang; Hou‐Zao Chen; Jinjing Liu; Yuyan Jia; Zhu‐Qin Zhang; Ruifeng Yang; Yuan Zhang; Jing Xu; Zhi‐Gang She; De‐Pei Liu; Chih‐Chuan Liang (2009)
SIRT1 (Sirtuin type 1), a mammalian orthologue of yeast SIR2 (silent information regulator 2), has been shown to mediate a variety of calorie restriction (CR)-induced physiological events, such as cell fate regulation via deacetylation of the substrate proteins. However, whether SIRT1 deacetylates activator protein-1 (AP-1) to influence its transcriptional activity and target gene expression is still unknown. Here we demonstrate that SIRT1 directly interacts with the basic leucine zipper domains of c-Fos and c-Jun, the major components of AP-1, by which SIRT1 suppressed the transcriptional activity of AP-1. This process requires the deacetylase activity of SIRT1. Notably, SIRT1 reduced the expression of COX-2, a typical AP-1 target gene, and decreased prostaglandin E(2) (PGE(2)) production of peritoneal macrophages (pMPhis). pMPhis with SIRT1 overexpression displayed improved phagocytosis and tumoricidal functions, which are associated with depressed PGE(2). Furthermore, SIRT1 protein level was up-regulated in CR mouse pMPhis, whereas elevated SIRT1 decreased COX-2 expression and improved PGE(2)-related macrophage functions that were reversed following inhibition of SIRT1 deacetylase activity. Thus, our results indicate that SIRT1 may be a mediator of CR-induced macrophage regulation, and its deacetylase activity contributes to the inhibition of AP-1 transcriptional activity and COX-2 expression leading to amelioration of macrophage function.